Double-ion-doped modified lithium manganate positive electrode material as well as preparation method and application thereof

By modifying lithium manganese oxide cathode material with dual ion doping, the problem of structural instability in lithium manganese oxide batteries was solved, improving its cycle performance and structural strength, and achieving higher specific capacity and excellent cycle performance.

CN119275278APending Publication Date: 2025-01-07LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310830970.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Lithium manganese oxide batteries experience rapid capacity decay during charging and discharging, mainly due to the dissolution of Mn3+ which damages the spinel structure, leading to structural instability.

Method used

By modifying lithium manganese oxide with dual ion doping, transition metal element A and fluoride element F are used to partially replace Mn and O in lithium manganese oxide, thereby improving structural stability and chemical bond strength, and preparing lithium manganese oxide cathode materials with a particle size of 9-12 μm.

Benefits of technology

It significantly improved the cycle performance and structural stability of lithium manganese oxide cathode materials, limited the Jiang-Taylor effect, and enhanced the structural strength and cycle stability of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275278A_ABST
    Figure CN119275278A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a double-ion-doped modified lithium manganate positive electrode material as well as a preparation method and application thereof. The chemical general formula of the double-ion doped modified lithium manganate positive electrode material is Li Mn < 2-b > AbF < c > O < 4-c >, wherein 1.03 < = a < = 1.15, 0.01 < = b < = 0.04, and 0.03 < = c < = 0.12; a is a transition metal element, the element A partially substitutes and occupies an octahedral Mn element in LiaMn2-bAbFcO4-c, the binding energy of the element A and an element O is greater than the binding energy of the element Mn and the element O, and the structural stability of the positive electrode material is improved by doping the element A; the element F partially replaces the element O, the chemical bond strength is improved by doping the element F, the lattice constant is reduced, and the structural strength of the positive electrode material is enhanced; the particle size of the dual-ion doped modified lithium manganate positive electrode material is 9-12 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a double-ion doped modified lithium manganate positive electrode material and a preparation method and application thereof. Background Art

[0002] As a green and clean battery, lithium-ion battery has the advantages of large specific capacity, high voltage and long life. At present, the mainstream batteries on the market are lithium cobalt oxide, lithium manganese oxide, nickel cobalt manganese ternary and lithium iron phosphate batteries.

[0003] Compared with batteries of other systems, lithium manganese oxide batteries have the advantages of low cost, safety, environmental protection and abundant raw material resources. However, the capacity of lithium manganese oxide batteries decays rapidly during the charging and discharging process, which restricts their application in the market.

[0004] The fundamental reason for the rapid capacity decay of lithium manganese oxide batteries in the early stage is that Mn 3+ The dissolution of Mn leads to the destruction of spinel structure. 3+ There is an electron in the t2g orbital, which will produce the Jiang-Taylor effect, causing the Mn-O octahedron to be distorted and stretched, further deepening the destruction of the lithium manganese oxide spinel structure.

[0005] This is because manganese ions (Mn 3+ ) has an electron in the t2g orbital among its d orbitals. In this case, the t2g orbitals refer to three of the five d orbitals of the manganese ion, namely the dxz, dyz, and dxy orbitals. According to Hund's rule, when there is only one electron in the t2g orbital, the electron will try to occupy different orbitals to maximize the spin multiplicity. This shows that in the t2g orbital, two of the dxz, dyz, and dxy orbitals will have no electrons, while the other orbital will have an electron. In transition metal ions with underfilled orbitals, due to the interaction between the electron spin freedom and the orbital freedom, the molecular or crystal structure is distorted to reduce the energy, which is the Chiang-Taylor effect. When the manganese ion (Mn 3+ ) has only one electron in the t2g orbital, the Jan-Taylor effect occurs. In lithium manganate spinel, manganese ions are surrounded by oxygen ions and form an octahedral coordination environment. In this case, Mn 3+ The single electron in the t2g orbital of the ion interacts with the coordinated oxygen atom. This interaction causes the deformation and stretching of the Mn-O octahedron, thereby destroying the lithium manganate spinel structure and causing the Mn-O octahedron to deform asymmetrically, making the structure unstable.

[0006] It is well known to those skilled in the art that the electrochemical performance of battery material compounds is closely related to the stability of the crystal structure. Therefore, such structural damage may affect the properties of lithium manganese oxide spinel materials. Summary of the invention

[0007] The purpose of the present invention is to provide a double ion doped modified lithium manganese oxide positive electrode material and its preparation method and application. The structural stability of the lithium manganese oxide positive electrode material is improved by double ion doping modification, thereby also making the modified lithium manganese oxide positive electrode material have a higher gram capacity and excellent cycle performance.

[0008] To this end, in a first aspect, an embodiment of the present invention provides a double-ion doped modified lithium manganese oxide positive electrode material, the general chemical formula of which is:

[0009] Li a Mn 2-b A b F c O 4-c ; Among them, 1.03≤a≤1.15, 0.01≤b≤0.04, 0.03≤c≤0.12;

[0010] A is a transition metal element. a Mn 2-b A b F c O 4-c The A element partially replaces the Mn element occupying the octahedral position, and the binding energy between the A element and the O element is greater than the binding energy between the Mn element and the O element, and the structural stability of the positive electrode material is improved by doping the A element;

[0011] The F element partially replaces the O element, and the chemical bond strength is increased by doping the F element, the lattice constant is reduced, and the structural strength of the positive electrode material is enhanced;

[0012] The particle size of the double-ion doped modified lithium manganate positive electrode material is 9 to 12 μm.

[0013] Preferably, the dual-ion doped modified lithium manganese oxide positive electrode material is a spinel phase.

[0014] Preferably, A is one or more of Mg, Zr, Nb, Y, Mo, Nd, and Ti.

[0015] In a second aspect, an embodiment of the present invention provides a method for preparing a double-ion doped modified lithium manganese oxide positive electrode material, comprising:

[0016] mixing an excess lithium source with an appropriate amount of a doping element compound and a manganese source to obtain a mixed material;

[0017] The mixed material is calcined to obtain the double-ion doped modified lithium manganese oxide positive electrode material.

[0018] Preferably, the lithium source is in excess of 3%-15% in molar ratio.

[0019] Preferably, the lithium source includes lithium hydroxide and / or lithium carbonate;

[0020] The manganese source includes one of α-MnO2, β-MnO2, R-MnO2, Mn2O3 and Mn3O4; the particle size of the manganese source is 5 to 9 μm;

[0021] The doping element compound includes fluoride of doping element A, or includes fluoride of doping element A and oxide of doping element A; the particle size of the doping element compound is 30-50 nm.

[0022] Preferably, the fluoride of the doping element A includes: one or more of MgF2, ZrCl4, NbF5, YF3, MoF5, NdF3 or TiF4;

[0023] The oxides of the doping element A include: MgO, ZrO2, Nb2O5, Y2O3, MoO3, Nd2O3, and TiO2.

[0024] Preferably, the mixing is carried out in a high-speed mixer, the mixing speed is 500 to 2000 r / min, and the mixing time is 5 to 50 min.

[0025] Preferably, the heating rate of the calcination is 3 to 6°C / min; the sintering temperature of the calcination is 650 to 850°C; and the holding time of the calcination is 10 to 20 hours.

[0026] In a third aspect, an embodiment of the present invention provides an application of a double-ion doped modified lithium manganese oxide positive electrode material, wherein the positive electrode material is applied to a positive electrode plate of a lithium ion battery.

[0027] The double ion doped modified lithium manganese oxide positive electrode material provided in the embodiment of the present invention improves the cycle performance of lithium manganese oxide by doping with two ions of A and F. The A element doped in the octahedral position partially replaces the Mn element, which reduces the Mn 3+ The binding energy between A and O is greater than that between Mn and O. Therefore, the structural stability of the positive electrode material can be improved by doping with A. The F element partially replaces the O element. The chemical bond strength is increased by doping with the F element, the lattice constant is reduced, and the structural strength of the positive electrode material is enhanced. In addition, the average valence state of the Mn element is further increased by lithium-rich doping. Through the above technical means, the Chiang-Taylor effect is limited and the cubic spinel structure of the positive electrode material is stabilized. Their synergistic effect can significantly improve the cycle stability of lithium manganese oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope image of the double-ion doped modified lithium manganese oxide positive electrode material prepared in Example 1 of the present invention;

[0029] Figure 2 This is an X-ray diffraction (XRD) diagram of the double-ion doped modified lithium manganate positive electrode material in Example 2 of the present invention;

[0030] Figure 3 The 100-cycle stability curve diagram of Example 1 of the present invention and Comparative Example 1 is shown. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0032] The embodiment of the present invention provides a double ion doped modified lithium manganese oxide positive electrode material, the chemical formula is: Li a Mn 2- b A b F c O 4-c ; Among them, 1.03≤a≤1.15, 0.01≤b≤0.04, 0.03≤c≤0.12; the double ion doped modified lithium manganese oxide positive electrode material is a spinel phase.

[0033] In specific examples, a may be 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1.13, 1.14 or 1.15; b may be 0.01, 0.02, 0.03 or 0.04; and c may be 0.03, 0.06, 0.09 or 0.12.

[0034] In the general formula, A is a transition metal element. a Mn 2-b A b F c O 4-c The Mn element occupying the octahedral position is partially replaced by the A element, and the binding energy between the A element and the O element is greater than the binding energy between the Mn element and the O element, and the structural stability of the positive electrode material is improved by doping the A element. Preferably, A is one or more of Mg, Zr, Nb, Y, Mo, Nd, and Ti. The F element partially replaces the O element, and the chemical bond strength is improved by doping the F element, the lattice constant is reduced, and the structural strength of the positive electrode material is enhanced.

[0035] The particle size of the double-ion doped modified lithium manganate positive electrode material of the present invention is 9 to 12 μm, for example, 9.0 μm, 9.4 μm, 9.8 μm, 10.2 μm, 10.6 μm, 11.0 μm, 11.4 μm, 11.8 μm or 12.0 μm.

[0036] The above materials can be prepared by the following preparation method:

[0037] The preparation method comprises: mixing an excess lithium source with an appropriate amount of a doping element compound and a manganese source to obtain a mixed material; and then calcining the mixed material to obtain a double-ion doped modified lithium manganate positive electrode material.

[0038] The above lithium sources are in excess of 3%-15% according to a molar ratio, and the lithium source may specifically include lithium hydroxide and / or lithium carbonate.

[0039] The manganese source includes one of α-MnO2, β-MnO2, R-MnO2, Mn2O3 and Mn3O4; the particle size of the manganese source is 5 to 9 μm, for example, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm.

[0040] The doping element compound includes a fluoride of the doping element A, or includes a fluoride of the doping element A and an oxide of the doping element A; wherein the fluoride of the doping element A includes one or more of MgF2, ZrF4, NbF5, YF3, MoF5, NdF3 or TiF4; the oxide of the doping element A includes MgO, ZrO2, Nb2O5, Y2O3, MoO3, Nd2O3, TiO2. The particle size of the doping element compound is 30 to 50 nm, for example, 30 nm, 40 nm or 50 nm.

[0041] The present invention can effectively improve the uniformity of mixing between materials by controlling the particle size of the doped element compound to be 30 to 50 nm. If the particle size of the doped element compound is less than 30 nm, the material has a large specific surface area and is prone to moisture absorption and agglomeration, which affects the dispersion effect of the material. If the particle size of the doped element compound is greater than 50 nm, it is not conducive to improving the uniformity of the mixture.

[0042] As a preferred technical solution of the present invention, mixing is carried out in a high-speed mixer, and the mixing speed is 500-2000 r / min, for example, 500 r / min, 800 r / min, 1100 r / min, 1400 r / min, 1700 r / min, 2000 r / min; the mixing time is 5-50 min, for example, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min.

[0043] As a preferred technical solution of the present invention, high temperature calcination is adopted for calcining the mixed material. The heating rate of calcination is 3-6°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min. The sintering temperature is 650-850°C, for example, 650°C, 680°C, 700°C, 720°C, 750°C, 770°C, 800°C, 820°C, 850°C. The holding time is 10-20h, for example, 10h, 12h, 15h, 18h, 20h.

[0044] The present invention prepares the spinel lithium manganese oxide positive electrode material by a high temperature calcination method with a high heating rate and a long heat preservation time. The primary particle prism structure of the lithium manganese oxide positive electrode material obtained by this high temperature calcination method is obvious and the boundary is flat and smooth, which is conducive to reducing Mn 3+ In addition, the long holding time is conducive to more effective doping of A and F elements into the lithium manganese oxide material, effectively improving the cycle stability of the material.

[0045] The double-ion doped modified lithium manganate positive electrode material of the present invention can be applied to the positive electrode sheet of a lithium ion battery.

[0046] In a specific example, a lithium-ion battery includes a double-ion doped modified lithium manganese oxide positive electrode material, a negative electrode material, a separator and an electrolyte. The preparation of the positive electrode material can be to use the modified lithium manganese oxide positive electrode material as an active material, mix it with a conductive agent Super P and a binder polyvinylidene fluoride (PVDF) in a mass ratio of 90:5:5 to obtain a positive electrode slurry, and then use an automatic coating machine to coat the positive electrode slurry on a current collector aluminum foil, and obtain a positive electrode sheet after drying. The positive electrode sheet, the separator and the lithium sheet are stacked and assembled in sequence to obtain a lithium-ion battery. The preparation of the battery positive electrode and the assembly of the battery described here are only for illustration and are not intended to limit the scope of the present invention.

[0047] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0048] Example 1

[0049] This embodiment provides a double ion doped modified lithium manganate positive electrode material, the molecular formula of which is Li 1.06 Mn 1.99 Y 0.01 F 0.03 O 3.97 , with a particle size of 10.2 μm. The preparation method of the double-ion doped modified lithium manganese oxide positive electrode material specifically comprises the following steps:

[0050] (I) Yttrium fluoride and manganese tetraoxide are weighed according to a stoichiometric ratio and mixed with 6% excess lithium carbonate in a high-speed mixer to obtain a mixture. The speed of the high-speed mixer is 1500 r / min and the mixing time is 20 min. The particle size of yttrium fluoride is 35 nm, the particle size of manganese tetraoxide is 5.8 μm, and the particle size of lithium carbonate is 5.3 μm.

[0051] (II) The mixture in step (I) was heated to 770°C at a heating rate of 4°C / min in a compressed air atmosphere, and the calcination holding time was 20h to obtain a double ion doped modified lithium manganate positive electrode material Li 1.06 Mn 1.99 Y 0.01 F 0.03 O 3.97 .

[0052] Example 2

[0053] This embodiment provides a double ion doped modified lithium manganate positive electrode material, the molecular formula of which is Li 1.09 Mn 1.98 Zr 0.0 1Mg 0.01 F 0.02 O 3.98 , with a particle size of 9.8 μm. The preparation method of the double-ion doped modified lithium manganese oxide positive electrode material specifically comprises the following steps:

[0054] (I) Magnesium fluoride, zirconium oxide and manganese tetraoxide are weighed in a stoichiometric ratio and mixed with 9% excess lithium carbonate in a high-speed mixer to obtain a mixture. The speed of the high-speed mixer is 1600 r / min and the mixing time is 25 min. The particle size of zirconium oxide is 50 nm, the particle size of magnesium fluoride is 48 nm, the particle size of manganese tetraoxide is 5.5 μm, and the particle size of lithium carbonate is 5.3 μm.

[0055] (II) The mixture of step (I) was heated to 750°C at a heating rate of 5°C / min in a compressed air atmosphere, and the calcination holding time was 18h to obtain a double ion doped modified lithium manganate positive electrode material Li 1.09 Mn 1.98 Zr 0.01 Mg 0.01 F 0.02 O 3.98 .

[0056] Example 3

[0057] This embodiment provides a double ion doped modified lithium manganate positive electrode material, the molecular formula of which is Li 1.11 Mn 1.97 Mg 0.0 1Nb 0.02 F0.02 O 3.98 , with a particle size of 10.0 μm. The preparation method of the double-ion doped modified lithium manganese oxide positive electrode material specifically comprises the following steps:

[0058] (I) Magnesium fluoride, niobium oxide and manganese tetraoxide are weighed according to a stoichiometric ratio and mixed with 11% excess lithium carbonate in a high-speed mixer to obtain a mixture. The speed of the high-speed mixer is 1400 r / min and the mixing time is 30 min. The particle size of magnesium fluoride is 38 nm, the particle size of niobium oxide is 32 nm, the particle size of manganese tetraoxide is 6.2 μm, and the particle size of lithium carbonate is 5.3 μm.

[0059] (II) The mixture of step (I) was heated to 700°C at a heating rate of 4°C / min in a compressed air atmosphere, and the calcination holding time was 15h to obtain a double ion doped modified lithium manganate positive electrode material Li 1.11 Mn 1.97 Mg 0.01 Nb 0.02 F 0.02 O 3.98 .

[0060] Example 4

[0061] This embodiment provides a double ion doped modified lithium manganate positive electrode material, the molecular formula of which is Li 1.12 Mn 1.99 Mg 0.01 F 0.02 O 3.98 , with a particle size of 10.6 μm. The preparation method of the double-ion doped modified lithium manganese oxide positive electrode material specifically comprises the following steps:

[0062] (I) Magnesium fluoride and manganese tetraoxide are weighed in a stoichiometric ratio and mixed with 12% excess lithium carbonate in a high-speed mixer to obtain a mixture. The speed of the high-speed mixer is 1600 r / min and the mixing time is 35 min. The particle size of magnesium fluoride is 32 nm, the particle size of manganese tetraoxide is 5.8 μm, and the particle size of lithium carbonate is 5.3 μm.

[0063] (II) The mixture of step (I) was heated to 800°C at a heating rate of 5°C / min in a compressed air atmosphere, and the calcination holding time was 22h to obtain a double ion doped modified lithium manganate positive electrode material Li 1.12 Mn 1.99 Mg 0.01 F 0.02 O 3.98 .

[0064] Example 5

[0065] This embodiment provides a double ion doped modified lithium manganate positive electrode material, the molecular formula of which is Li 1.09 Mn 1.98 Nd 0.0 1Y 0.01 F 0.03 O 3.97 , with a particle size of 9.8 μm. The preparation method of the double-ion doped modified lithium manganese oxide positive electrode material specifically comprises the following steps:

[0066] (I) weighing yttrium fluoride, tantalum oxide and manganese tetraoxide according to a stoichiometric ratio and mixing them with an excess of 9% lithium carbonate in a high-speed mixer to obtain a mixture, the speed of the high-speed mixer being 1500 r / min and the mixing time being 15 min;

[0067] (II) The mixture of step (I) was heated to 780°C at a heating rate of 5°C / min in a compressed air atmosphere, and the calcination holding time was 12h to obtain a double ion doped modified lithium manganate positive electrode material Li 1.09 Mn 1.98 Nd 0.01 Y 0.0 1F 0.03 O 3.97 .

[0068] Comparative Example 1

[0069] This comparative example provides a common lithium manganate positive electrode material with a molecular formula of Li 1.12 Mn2O4, particle size is 9.8μm. The preparation method of the lithium manganate positive electrode material specifically comprises the following steps:

[0070] (I) lithium carbonate and manganese tetraoxide are weighed in a desired stoichiometric ratio and mixed in a high-speed mixer to obtain a mixture. The speed of the high-speed mixer is 1600 r / min and the mixing time is 15 min;

[0071] (II) The mixture of step (I) is heated to a calcination temperature of 770° C. at a heating rate of 5° C. / min under a compressed air atmosphere, and the calcination holding time is 20 h to obtain the lithium manganate positive electrode material.

[0072] The double ion doped modified lithium manganese oxide positive electrode material prepared in Example 1 was subjected to electron microscopy scanning, and the scanning electron microscopy image is as follows: Figure 1 As shown, it can be seen that the lithium manganese oxide material is composed of relatively uniform-sized, angular, and prism-shaped primary particles tightly stacked, wherein the particle size of the primary particles is 1 to 3 μm; in addition, yttrium and fluorine are doped into the material to make the particle surface of the material smooth, thereby improving the structural strength of the particles and enhancing the cyclic stability of the material.

[0073] The double ion doped modified lithium manganese oxide positive electrode material prepared in Example 2 was subjected to XRD test. The XRD pattern is shown in FIG. Figure 2 As shown, it can be seen that the diffraction peak position and relative intensity of the double-ion doped modified lithium manganese oxide positive electrode material prepared in Example 2 are consistent with the standard cubic phase spinel structure, and no impurity peak appears, indicating that the modified lithium manganese oxide positive electrode material obtained in Example 2 is a spinel phase, and the structure of the lithium manganese oxide itself is not destroyed after doping.

[0074] The lithium manganese oxide positive electrode material obtained in the above-mentioned embodiments and comparative example 1 is used as the positive electrode active material, and it is mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 90:5:5 to obtain a positive electrode slurry. Use an automatic coating machine to coat the positive electrode slurry on the current collector aluminum foil with a coating thickness of 100μm, and obtain the positive electrode sheet after drying. The positive electrode shell, positive electrode sheet, diaphragm, electrolyte, negative electrode, gasket, spring and negative electrode shell are stacked and assembled in sequence to obtain a battery. Among them, the diaphragm uses a polypropylene (PP) base film, and the electrolyte uses a conventional lithium ion electrolyte 1M LiPF6 dissolved in a solution of ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) = 1:1:1. After the battery is assembled, it is cycled at 0.1C for 1 cycle in the voltage range of 3.0~4.3V, and then cycled 100 cycles at a rate of 1C. The 100-week cycle stability curve of the battery in Example 1 and Comparative Example 1 is shown as follows Figure 3 The test results of the 100-week cycle capacity retention rate and the first-week discharge capacity in grams of each embodiment are shown in

[0075] As shown in Table 1.

[0076]

[0077] Table 1

[0078] It can be seen from the above table:

[0079] Compared with Comparative Example 1, Examples 1-5 have higher gram capacities, better cycle stability, and significantly improved electrochemical performance.

[0080] According to Table 1 and Figure 3 The results of the cycle retention rate of 100 weeks at 0.1C show that the modified lithium manganese oxide positive electrode material of the present invention is significantly better than the ordinary lithium manganese oxide positive electrode material, indicating that the cycle performance of lithium manganese oxide is improved by doping with two ions of A and F. The A element doped in the octahedral position partially replaces the Mn element, which reduces the Mn 3+Since the binding energy between A and O is greater than that between Mn and O, the structural stability of the positive electrode material can be improved by doping with A. The F element partially replaces the O element, and the chemical bond strength is improved by doping with the F element, the lattice constant is reduced, and the structural strength of the positive electrode material is enhanced; in addition, the average valence state of the Mn element is further increased by lithium-rich doping. Through the above synergistic effects, the Chiang-Taylor effect is limited, the cubic spinel structure of the positive electrode material is stabilized, and the cycle stability of lithium manganate is significantly improved.

[0081] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A double ion doped modified lithium manganese oxide positive electrode material, characterized in that: The chemical formula of the double-ion doped modified lithium manganate positive electrode material is: Li a Mn 2-b A b F c O 4-c ; Among them, 1.03≤a≤1.15, 0.01≤b≤0.04, 0.03≤c≤0.12; A is a transition metal element. a Mn 2-b A b F c O 4-c The A element partially replaces the Mn element occupying the octahedral position, and the binding energy between the A element and the O element is greater than the binding energy between the Mn element and the O element, and the structural stability of the positive electrode material is improved by doping the A element; The F element partially replaces the O element, and the chemical bond strength is increased by doping the F element, the lattice constant is reduced, and the structural strength of the positive electrode material is enhanced; The particle size of the double-ion doped modified lithium manganate positive electrode material is 9 to 12 μm.

2. The double ion doped modified lithium manganate positive electrode material according to claim 1, characterized in that: The double-ion doped modified lithium manganate positive electrode material is a spinel phase.

3. The double ion doped modified lithium manganate positive electrode material according to claim 1, characterized in that: A is one or more of Mg, Zr, Nb, Y, Mo, Nd, and Ti.

4. A method for preparing a double-ion doped modified lithium manganese oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: mixing an excess lithium source with an appropriate amount of a doping element compound and a manganese source to obtain a mixed material; The mixed material is calcined to obtain the double-ion doped modified lithium manganese oxide positive electrode material.

5. The preparation method according to claim 4, characterized in that: The lithium source is in excess of 3%-15% by molar ratio.

6. The preparation method according to claim 5, characterized in that: The lithium source includes lithium hydroxide and / or lithium carbonate; The manganese source includes one of α-MnO2, β-MnO2, R-MnO2, Mn2O3 and Mn3O4; the particle size of the manganese source is 5 to 9 μm; The doping element compound includes fluoride of doping element A, or includes fluoride of doping element A and oxide of doping element A; the particle size of the doping element compound is 30-50 nm.

7. The preparation method according to claim 6, characterized in that: The fluoride of the doping element A includes: one or more of MgF2, ZrF4, NbF5, YF3, MoF5, NdF3 or TiF4; The oxides of the doping element A include: MgO, ZrO2, Nb2O5, Y2O3, MoO3, Nd2O3, and TiO2.

8. The preparation method according to claim 4, characterized in that: The mixing is carried out in a high-speed mixer, the mixing speed is 500 to 2000 r / min, and the mixing time is 5 to 50 min.

9. The preparation method according to claim 4, characterized in that: The heating rate of the calcination is 3-6°C / min; the sintering temperature of the calcination is 650-850°C; and the heat preservation time of the calcination is 10-20h.

10. An application of the double ion doped modified lithium manganese oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The positive electrode material is applied to the positive electrode sheet of a lithium ion battery.